A statistical approach to predict flexural strength and flame retardation properties for natural fibre/ epoxy composites - Noha Ramadan; Mohamed Taha; Ahmed Elsabbagh (Journal of Composite Materials, 2025)
This research investigates the development of a mathematical model to predict the influence of flame retardants (FR) on the mechanical and flame retardancy performance of natural fibre reinforced thermosetting composites. The study focuses on two types of FRs: Diammonium Phosphate (DAP) and silica fumes that were added to Jute reinforced epoxy composites (JRECs). Two mathematical models were established based on three variables and two measured responses. The variables include FRs type, FR content, and FR method of preparation, while the measured responses are Limiting oxygen index (LOI) and Flexural strength (FS). The models were developed using a statistical approach based on multiple linear regression fitting and validated using analysis of variance (ANOVA) technique. The developed models were verified using experimental result data from literature and the analysis of these models showed that the maximum discrepancy between the observed and predicted values for relative LOI and relative FS was within the range of ± 6% and ± 5%, respectively. This research contributes to the understanding of the impact of FRs on the mechanical and flame retardancy performance of natural fibre reinforced thermosetting composites, which can aid in the design and development of safer and more efficient composite materials.